ATIM-42. SAFETY AND EFFICACY OF AUTOLOGOUS DENDRITIC CELLS/TUMOR CELL ANTIGEN ADJUVANT THERAPY OF GLIOBLASTOMA MULTIFORME: RESULTS OF 59 CASES. (5th November 2018) - Huang, Yin-Cheng; Chang, Chen-Nen; Wei, Kuo-Chen; Lee, Han-Chung; Chen, Chun-Chung; Cho, Der-Yan; Yang, Wen-Kuang
Abstract: In our translational research, an immunotherapeutic, ADCTA-G, has been developed to emphasize autologous tumor antigens, DC antigen processing/presentation, enhanced tumor immunogenicity and CTL induction. Two clinical trials, Phase I/II [2003-2005Taiwan DOH/MA 0910072504] and phase II [2005–2016 NIH NCT02772094], "Dendritic Cell(DC)-Based Tumor Vaccine Adjuvant Immunotherapy of Human Glioblastoma Multiforme", respectively enrolled 17 and 42 WHO Grade-IV glioblastomas. Every patient received peripheral blood apheresis for PBMNCs. Monocytes were used for derivation of 3-7x108 phagocytic dendritic cells (iDC). Autologous glioma cells grown out of surgical tumor specimen were irradiated and co-cultivated 1 to 2:1 with iDC to make a ADCTA-G lot. After surgical tumor de-bulking, 10 vaccinations were given, each with 2-5x107 mature DC from the ADCTA lot, in a [4x biweekly and 6x monthly] scheduled s.c. injection in both axillar regions. The follow-up period has been 15 years. Primary endpoint is the overall survival (OS); phenotypes of tumor infiltrating T cells and tumor IDH mutation were also analyzed for long-term survivors. The ADCTA-G inoculations were tolerated well, and curtailed the grade-3/4 lymphopenia adverse effect of the temozolomide CCRT. The median OS is 22.9 months for the total 59 grade IV patients in the two trials. The median OS is 21.8 months for the 44 newly diagnosed patients and 28.1 months for the 15 recurrent patients; the difference is insignificant statistically. In this study, vaccinations were initiated early in the recurrent GBM patients while the newly diagnosed GBM patients had to wait till after external radiation therapy, leading to a comparable OS benefit of the ADCTA vaccination. Also, we demonstrated in vitro the earlier vaccinations in the recurrent decrease CD133+ tumor stem-like cells. In addition, the CD8(+) cells were susceptible to ionizing radiation. A phase 3 open-labelled randomized study will be initiated to improve the survival of this aggressive malignancy.